Treatment Of Iron In Groundwater Using Pebble Size And Sand Size Marble Column Filter - Khong, Ling Xin (Universiti Sains Malaysia, 2018)
Groundwater has always been a secondary water source in Malaysia. Water shortage during dry seasons had become a big issue that affecting the daily activities of the public. Groundwater is potentially a secondary water source that could ease the situation of water shortage since the current water supply comes from surface water. In Penang state, the water shortage issue does not happen frequently yet the new water resource should be explored to meet the demand of public water supply in future. In USM Engineering Campus, Nibong Tebal, there is groundwater resource beneath which has the potential to be developed for irrigation water use. This project studies about the pre-treatment of groundwater, which is removal of iron from the groundwater using pebble size and sand size marble column filter as referring to Wenworth particle size classification. The groundwater is treated using marble column filters to determine the removal of iron and other contaminant from the groundwater. Optimum flow rate is determined from the results of contaminants removal percentage when using different flow rate. In this project, the groundwater is sampled from the monitoring well located in USM Engineering Campus, Nibong Tebal. The marble used as filter media is high grade marble with 97.3% of CaCO3. Before the experiment is start, the groundwater is characterized using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) analysis whereas the marble is characterized by X-Ray Fluorescent (XRF) analysis and Scanning Electron Microscopy (SEM). The filtration is then run with 4 different flow rates which are 0.017, 0.011, 0.008 and 0.007 L s-1. ICP-OES analysis determines the initial and final concentration of iron and other element in the water sample. The results had reported 0.007 L s-1 as the most effective flow rate for iron removal in the groundwater. As seen from the results, pebble size marble is less effective in contaminant removal compare to sand size marble. The highest removal percentage of iron is for the sand size marble column filter when the flow rate is 0.007 Ls-1. The initial concentration of iron in the groundwater is 1.999 ppm but end up with 0.013 ppm of iron left in the water after filtrated. The marble is possible to be a cheap and effective filter media for iron removal in development of groundwater pre-treatment process in USM as the results show high removal for iron so as other element in the groundwater.